Jakarta Struts cookbook - Siggelkow, Bill (O'Reilly, 2005)
The Jakarta Struts Framework is a popular open source platform for building web applications from top to bottom with Java. While this popularity has led to a wealth of online and in-print documentation, developers still find themselves faced with a number of common tasks that are not clearly and succinctly explained. In these situations, programmers can now turn to the Jakarta Struts Cookbook an amazing collection of code solutions to common--and uncommon--problems encountered when working with the Struts Framework. Among many other recipes, this book explains how to: display data in compl.